Arc behaviour and metal transfer of the VP-GMAW process - Harwig, D. D. (Cranfield University, 2003)
This project evaluated the metal transfer behaviour of the variable polarity (VP) GMAW process. Analysis was performed using high speed video that was synchronised with high speed data acquisition. Melting rate measurements were found to be very dependent on current waveform, polarity, and droplet size, and metal transfer if it occurred, for each waveform period. The transient conditions of current waveform and metal transfer produced rapid changes in arc behaviour which influenced the melting at the electrode tip and growing droplet. The concentrated melting theory was developed to explain the significant increase in electrode extension burnoff and droplet growth rate that occurred at short EN time as a function of current, and during EP peak pulse when the pre-pulse droplet volume was small. The highest electrode extension burnoff and droplet growth rate occurred when the arc was permitted to climb over the solid electrode tip producing rapid concentrated melting. Likewise, large molten droplets were found to promote a negative electrode extension burnoff and a decreased droplet growth rate. The arc rooted on large droplets providing additional heating but limited electrode melting. The droplet burnoff rate (DBR) method was developed and found to yield good experimental measurements for the arc and resistive heating coefficients used in a 2nd order melting rate equation developed for a complex waveform process, like VP-GMAW. For the EN period, the EN time affected the melting rate as a function of EN current. The greater melting rate that occurred at low EN time was measured by the changes in the resistive heating coefficient. Concentrated arc melting of the electrode extension at low EN time caused the slope of the burnoff diagram to increase, which represented the resistive heating coefficient. The melting rate of the EP pulse was related to the pre-pulse droplet volume. Large pre-pulse droplets decreased the arc heating coefficient, which could be negative, which meant the electrode extension was increasing and the arc length was decreasing in that waveform period. VP-GMAW power supplies offered stable operation for welding sheet structures on both carbon steel and stainless steel. Higher travel speeds were required as the %EN of the waveform increased to produce acceptable constant deposit area fusion. Welding speeds were up to 300% higher with VP-GMAW compared to the GMAW-P process when welding lap joints on 1.8 mm thick material with a 1.8 mm gap. VP-GMAW heat input was up to 47% less than GMAW-P for the same melting rate.